An Examination of the P Requirements of Broiler Breeders for Performance, Progeny Quality and P Balance 2. Ca Particle Size - Ekmay, R.D.; Coon , C.N. (International Journal of Poultry Science, 2011)
A 2 x 5 factorial production and balance study with 90 broiler breeders was performed to assess the effects calcium particle size and NPP levels. Cobb 500 broiler breeders, 24 wk of age, were fed 4.68 g Ca intake at peak using 2 particle sizes of dietary calcium carbonate (185.5 microns; 58.8% solubility and 3489.7 microns; 38.5% solubility) and 5 levels of dietary %NPP (0.2% to 0.4% NPP in 0.05% increments; corresponding to a daily intake of 288, 360, 432, 504 and 576 mg at peak intake). Egg production, specific gravity and egg wt were monitored from 24 to 40 wk of age and tibia relative strength at 45 weeks. A retention study was performed at 31 wk of age to determine Ca and P balance. No differences were noted in breeder bone integrity due to NPP intake, though eggs per hen housed and egg shell quality were affected. The breeders fed 288 mg NPP produced the largest number of eggs. The % P retention showed a positive linear response to increasing dietary NPP for breeders fed large particle limestone; but no response in hens fed small particle limestone. The amount of P excreted was increased with P intake but was minimized for hens fed large particle limestone. The amount of Ca excreted was significantly increased with increasing P intake. There was a significant linear increase in excreta Ca and linear decrease in % Ca retention for breeders fed increasing P intake along with small particle calcium but the amount of Ca excreted and % Ca retention was not statistically impacted by particle size. Feeding breeders large particle calcium carbonate increased the egg weight but did not significantly improve shell quality or tibia bone strength. The increased egg weight response for breeders fed large particle calcium carbonate in this short term experiment may have reduced the opportunity for large particle Ca to significantly improve egg shell quality. It can be concluded that particulate Ca sources can improve breeder performance and that dietary levels as low as 0.20% NPP (288 mg/day NPP intake) can be fed without impacting breeder performance; however dietary levels of >0.25%NPP (360 mg/day NPP intake) ensure adequate skeletal integrity.